2016
DOI: 10.1007/s11162-016-9424-0
|View full text |Cite
|
Sign up to set email alerts
|

Postsecondary Student Persistence and Pathways: Evidence From the YITS-A in Canada

Abstract: The Youth in Transition Survey is used to follow the postsecondary education (PSE) pathways and outcomes of Canadian youth over the mid 2000s. Separate analyses are done for students who started at community colleges and those who started at four year universities. First program outcomes are reported, showing that significant numbers of students leave their first programs but remain in PSE by switching to other programs, institutions, or levels. Multinomial regression is used to estimate the correlates of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Recent research on non-academic abilities suggests that variables aside from past grades may help 1 Bound and Turner (2011)and Bound, Lovenheim and Turner (2010) discuss recent trends in the US, and Childs, Finnie and Martinello (2016) provide and analysis of Canadian trends. 2 Bettinger, Evans and Pope (2013); Dooley, Payne and Robb (2012); Cyrenne and Chan (2012); Rothstein (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on non-academic abilities suggests that variables aside from past grades may help 1 Bound and Turner (2011)and Bound, Lovenheim and Turner (2010) discuss recent trends in the US, and Childs, Finnie and Martinello (2016) provide and analysis of Canadian trends. 2 Bettinger, Evans and Pope (2013); Dooley, Payne and Robb (2012); Cyrenne and Chan (2012); Rothstein (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the determinants of completion using YITS data have examined social structures, student characteristics, and institutional features (Lambert, Zeman, & Allen, 2004). These studies reported a positive association between high school grades and degree completion (Christofides, Hoy, Milla & Stengos, 2015), as well as positive relationships between graduation and family socio-economic status (SES), being female, and attending an urban school (Childs, Finnie, & Martinello, 2017). Due to sampling limitations in YITS, however, ethnic or racial differences were not examined or were aggregated and treated as a single 'visible minority' category (e.g., Thiessen, 2009).…”
Section: Determinants Of Ba/bsc Degree Completionmentioning
confidence: 99%
“…Among individuals who enroll in a bachelor's degree (BA/BSc) program, fewer than two-thirds complete their studies within 6 years (Childs, Finnie, & Martinello, 2017;Heslop, 2015). This disjuncture in admission and graduation rates raises policy concerns around government expenditures, institutional effectiveness, and high school graduates' academic preparedness for post-secondary education (PSE) (Ministry of Training, Colleges and Universities, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Student success in post-secondary education is an ongoing concern, likely because of numerous factors, including Canadian government funding models focused on student success and attrition (Childs, Finnie, & Martinello, 2017;Ministry of Training, Colleges and Universities, 2015). A wave of recent Canadian research on post-secondary attendance has emerged from the Youth in Transitions Survey, focusing on factors that predict attendance and persistence Jerrim & Vignoles, 2015), but Canadian research on predictors of student success (i.e., average grades) appears to be more limited.…”
Section: Predictors Of Student Success In Non-university Post-secondamentioning
confidence: 99%